2004
DOI: 10.1023/b:mcbi.0000012853.20116.06
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid oxidation and related gene expression in heart depleted of carnitine by mildronate treatment in the rat

Abstract: The metabolic and genic effects induced by a 20-fold lowering of carnitine content in the heart were studied in mildronate-treated rats. In the perfused heart, the proportion of palmitate taken up then oxidized was 5-10% lower, while the triacylglycerol (TAG) formation was 100% greater than in controls. The treatment was shown to increase the maximal capacity of heart homogenates to oxidize palmitate, the mRNA level of carnitine palmitoyltransferase I (CPT-I) isoforms, the specific activity of CPT-I in subsarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 65 publications
3
19
0
3
Order By: Relevance
“…Because CPT I catalyzes the key step of the mitochondrial FA oxidation pathway, and necessarily requires carnitine for its activity, a decrease in FA oxidation rates through mildronate treatment was expected in mitochondria of all organs. Yet, the expected decreased FA oxidation in muscle of mildronate-treated rats used in the fasted or fed state was never associated with any lipid infiltration (44). This suggests that the increased FA esterification due to artificial inhibition of FA oxidation in the perfused liver of normal rats used upon fasting (20) was quantitatively of too low extent to trigger steatosis, but was sufficient to initiate, in the whole body of mildronate-treated rats, regulations amplifying the lipid flux to liver and finally producing liver steatosis.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Because CPT I catalyzes the key step of the mitochondrial FA oxidation pathway, and necessarily requires carnitine for its activity, a decrease in FA oxidation rates through mildronate treatment was expected in mitochondria of all organs. Yet, the expected decreased FA oxidation in muscle of mildronate-treated rats used in the fasted or fed state was never associated with any lipid infiltration (44). This suggests that the increased FA esterification due to artificial inhibition of FA oxidation in the perfused liver of normal rats used upon fasting (20) was quantitatively of too low extent to trigger steatosis, but was sufficient to initiate, in the whole body of mildronate-treated rats, regulations amplifying the lipid flux to liver and finally producing liver steatosis.…”
Section: Discussionmentioning
confidence: 87%
“…One-step cDNA synthesis and conventional PCR were performed as described in Ref. 44. Primer pairs were designed using "Primers!"…”
Section: Gene Expressionmentioning
confidence: 99%
“…However, recent work (Zaugg et al, 2003) on carnitine-depleted adult rats demonstrated that mildronate treatment caused abnormalities in myocardial functions, including systolic dysfunction, reduced contractile reserve, and a blunted frequency-force relationship. Degrace et al (2004) studied fatty acid oxidation and related gene expression in hearts depleted of carnitine by mildronate treatment in adult rats. They observed that mildronate was able to decrease the whole heart carnitine content without affecting mitochondrial carnitine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Le CLA2 étant un bon substrat pour les réac-tions d'élongation/désaturation [27] et pour la production d'eicosanoïdes [28], il est tout à fait envisageable que des métabolites du CLA2 soient à l'origine de certains des effets attribués à cet isomère. Quoi qu'il en soit, une augmentation de l'activité oxydative, mesurée in vitro, peut ne pas refléter la réalité physiologique et peut même, au contraire, traduire un déficit oxydatif comme cela était le cas dans le foie de rats déficients en carnitine [30]. Ainsi, pour tenter d'évaluer les activités oxydatives in vivo, il est indispensable de prendre en considération les étroites relations qui lient les voies de la lipogenèse à celles de l'oxydation.…”
Section: Effets Sur La ß-Oxydation Des Acides Gras à Longue Chaîne (Aunclassified
“…En effet, la concentration élevée en malonyl-CoA associée à la forte sensibilité de la CPT I observée chez les souris traitées doivent conduire à une déviation des AG vers les voies d'estérification. De plus, les augmentations d'activité et d'expression de la CPT I mesurées chez les souris exposées au CLA2 plaident paradoxalement en faveur d'une réduction de l'oxydation in vivo puisque de telles inductions interviennent générale-ment dans des conditions physiologiques inhibitrices (à l'état nourri) ou pharmacologiques [30]. …”
Section: Effets Du Cla2 Sur La Lipogenèse Et Conséquences Sur Les Tauunclassified